(untitled) (Ukrainian Journal of Ophthalmology, 2023)
The study based on the literature search revealed that the peculiarities of fluid circulation in the posterior part of the eye have been studied insufficiently compared to the anterior part. It is suggested that the retina and optic nerve have their own cleansing system, which functions independently or in interaction with the brain’s cleansing system. Of interest is the theory of the glymphatic system of the eye, which probably functions similarly to the glymphatic system of the brain, has four segments and ensures the exchange between intraocular, intracranial and interstitial fluids and the removal of metabolic waste products in the posterior part of the eye. Purpose. To determine the disorders of fluid circulation in the posterior part of the eye in the mechanisms of optic nerve damage development according to the literature. Methods: literature search of 48 sources. It is important to understand that the optic nerve under normal conditions passes a large amount of fluid from the eye to the brain and vice versa. The balance of perfusion (and, presumably, reperfusion in case of pathology) is ensured by the lamina cribrosa, the location of subarachnoid spaces in different parts of the nerve, and the AQP4 channels that support them. The question is whether the optic nerve has its own separate glymphatic system, or whether it interacts with the glymphatic system of the brain. It also remains unclear how the circulation of intraocular fluid, interstitial fluid of the retina and brain, and cerebrospinal fluid in the optic nerve is coordinated with blood, as well as with fluctuations in atmospheric pressure. Although this theory has not yet been recognized, it nevertheless has many supporters who explain optic nerve damage as a result of fluid circulation disturbances. The slowing of fluid flow, as well as the slowing of axonal transport, can be considered as the moment when neuropathy transforms into optic atrophy. That is why the study of the peculiarities of fluid flow and exchange in the posterior part of the eye is important when studying diseases of the optic nerve, whereas the correction of such circulation disorders could be used for therapeutic purposes. Conclusion. Impaired fluid circulation in the posterior part of the eye can occur in mechanisms of optic nerve damage. Improved diagnostics with the ability to assess hydrodynamics will help to understand the role of individual components, while their correction will likely contribute to the optic nerve recovery.